Comparative Analysis of Machine Learning and Artificial Intelligence Algorithms for Pharmaceutical Demand Forecasting in Hospital Supply Chains: A Case Study at Hospital X - Purnomo, Doni; Sakti, Intan Widuri; Gustiana, Iyan (VOCATECH: Vocational Education and Technology Journal, 2025)
AbstractHealthcare systems in Indonesia face unique challenges due to diverse geographical landscapes and high dependency on pharmaceutical imports, resulting in complex demand forecasting requirements. This study proposes an innovative approach to pharmaceutical demand forecasting by leveraging Machine Learning (ML) and Artificial Intelligence (AI) techniques to optimize hospital supply chains. A comparative evaluation of six forecasting algorithms was conducted using 650 days of pharmaceutical transaction data from Hospital X, encompassing 374,171 dispensing events. The study compared traditional time series methods (Simple Moving Average, Weighted Moving Average, Exponential Smoothing) with advanced ML algorithms (Linear Regression, Support Vector Regression, Deep Learning LSTM). Results demonstrate that the Deep Learning model achieved superior performance with MAPE of 2.35%, representing a 34.4% improvement over traditional methods. The integrated feature engineering architecture successfully captured temporal and seasonal patterns specific to tropical healthcare environments. Implementation of the ML-based forecasting system shows potential for 25-30% reduction in safety stock requirements while maintaining 99.5% service levels, translating to significant cost savings and improved drug availability in Indonesian hospital settings AbstrakSistem pelayanan kesehatan di Indonesia menghadapi tantangan kompleks yang dipengaruhi oleh kondisi geografis yang beragam serta tingginya ketergantungan terhadap impor produk farmasi. Hal ini berdampak langsung pada kompleksitas dalam proses peramalan permintaan obat di rumah sakit. Penelitian ini mengusulkan pendekatan inovatif dalam peramalan permintaan farmasi dengan memanfaatkan teknik Machine Learning (ML) dan Artificial Intelligence (AI) guna mengoptimalkan rantai pasok rumah sakit. Evaluasi komparatif terhadap enam algoritma peramalan dilakukan menggunakan data transaksi farmasi selama 650 hari dari Rumah Sakit X, yang mencakup 374.171 data pemberian obat.Metode yang dibandingkan mencakup pendekatan deret waktu konvensional (Simple Moving Average, Weighted Moving Average, dan Exponential Smoothing) serta algoritma pembelajaran mesin tingkat lanjut (Regresi Linier, Support Vector Regression, dan Long Short-Term Memory atau LSTM). Hasil penelitian menunjukkan bahwa model Deep Learning LSTM menghasilkan performa terbaik dengan nilai Mean Absolute Percentage Error (MAPE) sebesar 2,35%, atau meningkat 34,4% dibandingkan dengan metode konvensional. Arsitektur rekayasa fitur yang digunakan mampu mengidentifikasi pola musiman dan temporal yang khas di lingkungan kesehatan tropis. Implementasi sistem peramalan berbasis ML ini menunjukkan potensi pengurangan kebutuhan safety stock sebesar 25–30%, dengan tetap mempertahankan tingkat layanan sebesar 99,5%. Temuan ini menunjukkan peluang penghematan biaya yang signifikan dan peningkatan ketersediaan obat di rumah sakit Indonesia.